Transnational Corporations and Human Rights - Muhammed, Muhammed Hamid (UI Scholars Hub, 2021)
International trade has introduced many features in its classical or contemporary practice wherein peoples respectfully exchanged goods and ideas. Unfortunately, the legacy of large multinational corporations, concerning human rights, has generally been dismal. It is recognised that states are the primary bearers of responsibility to respect, protect, fulfill, and promote human rights and freedoms. Current developments in the field of international human rights law, however, designated transnational corporations (hereafter TNCs), organisations, and individuals in a diagonal and/or horizontal responsibility on the respect and protection of human rights. The need to make these non-state actors, especially TNCs, responsible under international law is originated from their ever-increasing influence on state actors and their impact on the individuals’ enjoyment of their social, political, and economic rights. This article deals with the multidimensional influence of TNCs on the respect, protection, and fulfilment of fundamental human rights and demonstrates the possibilities of building legal obligation over them by reviewing existing literature.